Crystallographic orientation relationships in the α→γ′ martensitic transformation in an Fe-Mn-Al-Ni system - Vallejos, Juan Manuel (2018)
The Fe43.5Mn34Al15Ni7.5 (at.%) alloy exhibits outstanding pseudoelastic behaviour over a wide range of temperatures. This alloy undergoes an unusual martensitic transformation from a disordered body-centred cubic (α) parent phase to a face-centred cubic γ′) product phase. In the present work, the orientations of the parent and product phases for quenched samples were analysed by electron backscatter diffraction. Bain, Kurdjumow-Sachs, Pitsch, Nishiyama-Wassermann and Greninger-Troiano orientation relationships between the parent and product phases were compared with experimental results. The Pitsch relationship appears to be the most suitable to describe the α→γ′ martensitic transformation. This result provides experimental support to the dislocation-based heterogeneous Bogers-Burgers type transformation mechanism. No indications of variant selection were detected in the thermally activated transformations.